On Exponential Stability of Composite Stochastic Control Systems. (20th March 2013) - Abedi, Fakhreddin; Leong, Wah June
Abstract : New results for exponential stability in probability of a composite stochastic control system are established. The main results of this paper enable us to derive sufficient conditions for exponential stability inr -th mean and almost sure exponential stability in probability of composite stochastic control system. Two numerical examples are given to illustrate the results.